Capacity Building and Financing Oral Health in the African and Middle East Region. (July 2015) - Mumghamba, E.G.; Joury, E.; Fatusi, O.; Ober-Oluoch, J.; Onigbanjo, R.J.; Honkala, S.
Many low- and middle-income countries do not yet have policies to implement effective oral health programs. A reason is lack of human and financial resources. Gaps between resource needs and available health funding are widening. By building capacity, countries aim to improve oral health through actions by oral health care personnel and oral health care organizations and their communities. Capacity building involves achieving measurable and sustainable results in training, research, and provision of care. Actions include advancement of knowledge, attitudes and skills, expansion of support, and development of cohesiveness and partnerships. The aim of this critical review is to review existing knowledge and identify gaps and variations between and within different income levels in relation to the capacity building and financing oral health in the African and Middle East region (AMER). A second aim is to formulate research priorities and outline a research agenda for capacity building and financing to improve oral health and reduce oral health inequalities in the AMER. The article focuses on capacity building for oral health and oral health financing in the AMER of the IADR. In many communities in the AMER, there are clear and widening gaps between the dental needs and the existing capacity to meet these needs in terms of financial and human resources. Concerted efforts are required to improve access to oral health care through appropriate financing mechanisms, innovative health insurance schemes, and donor support and move toward universal oral health care coverage to reduce social inequality in the region. It is necessary to build capacity and incentivize the workforce to render evidence-based services as well as accessing funds to conduct research on equity and social determinants of oral health while promoting community engagement and a multidisciplinary approach.